2019
DOI: 10.1136/bcr-2019-229481
|View full text |Cite
|
Sign up to set email alerts
|

Congenital thrombotic thrombocytopenic purpura presenting in adulthood with recurrent cerebrovascular events

Abstract: Congenital thrombotic thrombocytopenic purpura (cTTP) is a rare, life-threatening disease, characterised by episodes of microangiopathic haemolytic anaemia (MAHA), thrombocytopenia and small vessel thrombosis. We describe a case of cTTP first diagnosed at age 70 years in a female presenting with an acute ischaemic stroke and thrombocytopenia, in whom A Disintegrin And Metalloproteinase with a Thrombospondin type 1 Motif, member 13 (ADAMTS13) levels were <10%, suggestive of thrombotic thrombocytopaenic purpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Prophylactic treatment was reported for 110 (53%) of the 207 symptomatic patients who survived infancy. Prophylaxis began at a median age of 14 years (range, newborn 21 -70 23 years). Prophylaxis was almost always with plasma, commonly described as 1 to 3 units of plasma at 2- to 3-week intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic treatment was reported for 110 (53%) of the 207 symptomatic patients who survived infancy. Prophylaxis began at a median age of 14 years (range, newborn 21 -70 23 years). Prophylaxis was almost always with plasma, commonly described as 1 to 3 units of plasma at 2- to 3-week intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the prolonged course of treatment in our patient, studies showed that high titers of inhibitors of ADAMTS-13 are associated with delayed response to therapy, high risk of complications, and higher rates of refractory disease and relapses [ 19 , 20 ]. Of note, while there are reports of patients with TTP who presented with IS as an atypical presentation [ 15 , 21 ], there are very few reports of new ischemic lesions during hospitalization following the first ischemic stroke event [ 14 , 15 ]. One was a 70-year-old female who presented with confusion, fever, and gastrointestinal symptoms who deteriorated neurologically during hospitalization, and the brain MRI revealed multiple acute and subacute infarcts in both cerebral hemispheres, midbrain, and right cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…One was a 70-year-old female who presented with confusion, fever, and gastrointestinal symptoms who deteriorated neurologically during hospitalization, and the brain MRI revealed multiple acute and subacute infarcts in both cerebral hemispheres, midbrain, and right cerebellum. The patient had a history of hypertension, diabetes, rheumatoid arthritis, two miscarriages complicated by disseminated intravascular coagulation, two transient ischemic attacks, and a left occipital infarct and she was diagnosed with congenital TTP [ 14 ]. Another one was a 43-year-old female who was admitted with left hemiparesis, homonymous hemianopia, and dysarthria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations